2013
DOI: 10.4028/www.scientific.net/amr.690-693.1891
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Bearing Capacity Influence due to Location of Bearing Push-Extend Reamed of the Push-Extend Multi-under-Reamed Pile

Abstract: Because the failure behavior of the soil surrounding the Push-extend Multi-under-reamed Pile will be affected by the placed location of the bearing push-extend reamed, further, the bearing capacity of the Pile is affected, in the paper, through experimental study and theoretical analysis, it is qualitatively analyzed that the influence of the location of the bearing push-extend reamed for the bearing capacity of the Push-extend Multi-under-reamed Pile, the achievements of the paper will present the well theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(Y. Qian et al) showed that tensile stress is developed in the soil on top of the bearing under-reamed bulb, and the side friction of the pile has been lost in this region. To fully exert the action of the bearing under-reamed bulb and side friction resistance of the pile, the location of the bearing under-reamed bulb should be near the top of the pile [14]. (Xie and Yin) studied the influence of bulbs' spacing on the under-reamed pile and found that when the spacing is less than 2Du, the soil between the bulbs is crushed because the bulbs' spacing is too small and the soil is too thin, which leads to the pile not working effectively.…”
Section: -Introductionmentioning
confidence: 99%
“…(Y. Qian et al) showed that tensile stress is developed in the soil on top of the bearing under-reamed bulb, and the side friction of the pile has been lost in this region. To fully exert the action of the bearing under-reamed bulb and side friction resistance of the pile, the location of the bearing under-reamed bulb should be near the top of the pile [14]. (Xie and Yin) studied the influence of bulbs' spacing on the under-reamed pile and found that when the spacing is less than 2Du, the soil between the bulbs is crushed because the bulbs' spacing is too small and the soil is too thin, which leads to the pile not working effectively.…”
Section: -Introductionmentioning
confidence: 99%